Carp Edema Virus/Koi Sleepy Disease: An Emerging Disease in Central‐East Europe. Issue 1 (8th November 2014) - Lewisch, E.; Gorgoglione, B.; Way, K.; El‐Matbouli, M.
Summary Koi sleepy disease (KSD), also known as carp edema virus (CEV), was first reported from juvenile colour carp in Japan in the 1970s. Recently, this pox virus was detected in several European countries, including Germany, France and the Netherlands. In England, in addition to colour carp, outbreaks in common carp are reported. KSD/CEV is an emerging infectious disease characterized by a typical sleepy behaviour, enophthalmia, generalized oedematous condition and gill necrosis, leading to hypoxia. High mortality, of up to 80–100%, is seen in juvenile koi collected from infected ponds. In Austria, this disease had not been detected until now. In spring 2014, diagnostic work revealed the disease in two unrelated cases. In one instance, a pond with adult koi was affected; in the other, the disease was diagnosed in adult common carp recently imported from the Czech Republic. A survey was carried out on recent cases (2013/2014), chosen from those with similar anamnestic and physical examination findings, revealing a total of 5/22 cases positive for KSD/CEV. In this study, two paradigmatic cases are presented in detail. Results together with molecular evidence shaped the pattern of the first diagnosis of KSD/CEV in fish from Austrian ponds. In the light of the positive cases detected from archived material, and the spread of the disease through live stock, imported from a neighbouring country, the need for epidemiological investigations in Austria and surrounding countries is emphasized.